Towards a model of software development process for a physically distributed environment - Audy, Jorge Luis Nicolas (2002)
The goal of this article is to present the first results of a study looking forward to propose a model of software development for a physically distributed environment (United States and Brazil). Thus, the objective is to combine empirical and theoretical knowledge in the software development area, aiming to minimize communication problems found in this specific environment. As result, the article proposes the addition of two new phases in the software development process, planning and evaluation, based on Unified Process and the UML language. The purpose is to demonstrate through illustrations and discussions, how these two phases are engaged in the process as a whole and what they represent. Some points open to discussion, which are themes for future researches, are identified, aiming to propose a model of software development for a physically distributed environment. The empirical basis of the study involves the EBusiness Research Center, a partnership of Dell Computers with PUCRS.